ASSESSMENT OF THE EFFECT OF ALPHA-GALACTOSIDES ON YOLK SAC RESORPTION RATE IN BROILER CHICKENS - A. Brudnicki; R. Szymeczko; M. Bednarczyk; B. Głowińska; D. Pietruszyńska (Journal of Animal and Plant Sciences, 2015)
The aim of the present study was to investigate the effect of the injection of raffinose-family oligosaccharides during embryogenesis on the rate of resorption of the yolk sac. 80 000 eggs were divided in two groups, the control and the experimental; 40 000 eggs in each. The experimental group eggs were injected on the 12th day of hatch directly into the air cell with the substance containing α–galactosides. The yolk sac's were sampled right after slaughter from earlier weighed, 1, 4, 7 and 14-day chickens, from 10 broilers each time.  In the investigation the parameters of yolk sac were e.g. yolk sac/body weight ratio and the egg yolk absorption. Moreover, there was also evaluated mean body weight, feed conversion ratio, mortality rate and the European Efficiency Ratio. Results showed that the single injection have a favourable effect on yolk sac resorption rate. Yolk sac/body weight ratio decreased and the estimated yolk absorption increase in experimental group. Also better indicators of production were found in the experimental group.
Keywords: α-galactosides; in ovo; poultry production; preobiotic